PENERAPAN PEMBERIAN NEBULIZER PADA PASIEN PNEUMONIA DI RUMAH SAKIT TKII PUTRI HIJAU MEDAN - Ummi, Nurhasanah; Susyanti, Deni; Gea, Handerman Vitu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Pneumonia is an acute infection that affects the lower respiratory tract, particularly the lungs, caused by various microorganisms such as pneumococcus, staphylococcus, streptococcus, and viruses. In patients with pneumonia, a common nursing problem is ineffective airway clearance due to the presence of foreign substances resultingfrom excessive secretion buildup caused by infection, immobility, and ineffective coughing. Administration of nebulizer inhalation therapy is a collaborative treatment aimed at relieving bronchospasm, thinning secretions, clearing the airway, and moisturizing the respiratory tract, thereby optimizing breathing. This study aims to provide medical-surgical nursing care through the administration of nebulizer therapy in pneumonia patients. The research method used is a descriptive design with a case study approach involving two patients diagnosed with pneumonia at TK 111 Putri Hijau Hospital, Medan. The case study in this research implements the medical-surgical nursing care process, which includes assessment, nursing diagnosis, intervention and implementation of nebulizer inhalation therapy, and evaluation. The inclusion criteria were pneumonia patients willing to become respondents and experiencing ineffective airway clearance. The results showed that the application ofnebulizer therapy was effective in addressing ineffective airway clearance in both patients with pneunlonia. Therefore, the implementation of nebulizer therapy is recommendedfor nursing practice